Replica de factores en el inventario de replica de intereses profesionales de Hereford (IIPH) - Fernandez, Gustavo; Lara Tapia, Luis; Hereford, Carl F. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Two administrations of the IIPH to Mexican students at high school levels were used in order to test the factorial structure of the inventory and the possibility of factors replication. Four of the areas of vocational interest turned out to be consistent in their factorial structure: Cálculo, Mecánico, Musical and Plástico. The two areas belonging to the scientific realm (Biológico and Físico) need revision of items if their factorial fitness is desired. The four "humanistic" areas (Verbal, Literario, Ejecutivo Persuasivo and Servicio Social) cannot be considered as factorially valid. The verbal area, recently dropped from the test, showed such high correlations with the rest of the areas that its elimination may be safely considered as a wise measure.